Unemployment, Employment, and Wage Rates Continued to Improve for Aboriginals in 2018 - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2019)
Employment, unemployment and wage rates improved for Aboriginals in Canada in 2018, while their participation rate decreased. For non-Aboriginals unemployment and wage rates also improved; however, their employment rate was unchanged, and their participation rate decreased. All four of these employment measures, which are employment, unemployment, participation, and wages, rates are and historically have been more favourable for non-Aboriginals than for Aboriginals. The differences in employment and wage rates are partially explained by the education level completed. The measures of employment are examined by gender, age, province, economic sector, education, and for Métis, First Nations, and Inuit.